Fundamentals of gas shale reservoirs - Rezaee, Reza (John Wiley and Sons, Inc., 2015)
Provides comprehensive information about the key exploration, development and optimization concepts required for gas shale reservoirs -Includes statistics about gas shale resources and countries that have shale gas potential -Addresses the challenges that oil and gas industries may confront for gas shale reservoir exploration and development -Introduces petrophysical analysis, rock physics, geomechanics and passive seismic methods for gas shale plays -Details shale gas environmental issues and challenges, economic consideration for gas shale reservoirs -Includes case studies of major producing gas shale formations.